Eficiência de telas de arame na segregação de aves de vida livre para a biossegurança de aviários comerciais, Brasil, 2010 - Guilherme Rocha Vianna (2010)
This study aimed to evaluate the efficiency of different mesh-sized wire meshes for the biosecurity of the poultry industry chicken houses. Brazilian poultry in technically advanced and employs updated technology, and in spite of the recent agriculture Act, recommending for the 25,4 mm mesh, no scientific proof is available of its efficiency. A methodology was developed for the relation of bird species and for the analysis of data. Five hundred and six (506) birds, representing 23 species most common around chicken houses were evaluated. Five chain-link and two hexagonal mesh were used. Three groups of bird species were formed a according to an archetype of importance, estimated by the ability of passage. The best efficiency wasobserved for mesh 19,11 mm capable of restraining all species study. However the presently adequate mesh (25,4 mm) could not retain Passer domesticus, Carduelis magellanicus, Sporophila caerulescens, Sporophila lineola, Sporophila nigricollis, Volatina jacarina, Sporophilaplúmbea, Sporophila leucoptera, Sporophila collaris, Sporophila bouvereuil, Sporophila angolensi.The proposed mesh for the biosecurity of poultry houses was inefficient and the propose of free-living, especially the house sparrow, represented a sanitary risk ( ex. avian influenza).